Scoping the Development of Implementing an Undergraduate Operating Department Practitioners Buddy Scheme - Crisp, Elizabeth; Latham, Callum; Phillips, Charlotte; Smith, Hazel A; Olukun, Olutayo Isaac; Gurney, Elizabeth; Wilton, Kelly; Woodrow-Hirst, Ben; Jones , Sarahjane (The Journal of Practice Teaching and Learning, 2024)
Introduction: In England, higher education institutions (HEIs) are modifying their processes to implement support strategies to decrease attrition rates. Some HEIs offer student buddy schemes to foster support networks, and knowledge exchange, build friendships, and increase confidence. Buddy schemes include peer-to-peer support coordinated by institutions, pairing experienced and non-experienced individuals aimed to provide support, advice, and training. At present, there is a lack of evidence capturing Operating Department Practitioner (ODP) students’ opinions about the implementation of a buddy scheme to improve student retention. Thus, to address this gap, a qualitative study with second year ODP students was undertaken. Methods: Nine second year ODP students in the Midlands, England attended two focus groups. Questions relating to students’ thoughts and perceptions of barriers, and facilitators to a buddy scheme guided the discussion. All focus groups were audio-recorded and transcribed verbatim, and data were analysed using reflexive thematic analysis. Results: All students regarded the buddy scheme to be potentially advantageous. The reflexive thematic analysis identified three main themes: (1) the value of having a buddy in supporting wellness; (2) the sharing of students’ experiences; and (3) the structure of the buddy scheme. Implications For Practice: All participants agreed that a buddy scheme would greatly support fellow students both academically and professionally. ODP students see buddy schemes as critical for support and shared experience in completing their studies. Co-design is vital for developing the buddy scheme for ODP students, and further studies are needed to inform the effectiveness of evidence-based buddy schemes.